Circulating LPS and (1→3)-β-D-Glucan: A Folie à Deux Contributing to HIV-Associated Immune Activation - Ramendra, Rayoun; Isnard, Stéphane; Mehraj, Vikram; Chen, Jun; Zhang, Yonglong; Finkelman, Malcolm; Routy, Jean-Pierre (Frontiers in Immunology, 2019)
Immune activation is the driving force behind the occurrence of AIDS and non-AIDS events, and is only partially reduced by antiretroviral therapy (ART). Soon after HIV infection, intestinal CD4 T cells are depleted and epithelial gut damage occurs leading to subsequent translocation of microbes and/or their products, which contributes to systemic immune activation. Bacteria and fungi are the two most abundant populations of the gut microbiome. Circulating lipopolysaccharide (LPS) and (1->3)-B-D-Glucan (BDG), major components of bacterial and fungal cell walls respectively, are measured as markers of microbial translocation in the context of compromised gut barriers. While LPS is a well-known inducer of innate immune activation, BDG is emerging as a significant source of monocyte and NK cell activation that contributes to immune dysfunction. Herein, we critically evaluated recent literature to untangle the respective roles of LPS and BDG in HIV-associated immune dysfunction. Furthermore, we appraised the relevance of LPS and BDG as biomarkers of disease progression and immune activation on ART. Understanding the consequences of elevated LPS and BDG on immune activation will provide insight into novel therapeutic strategies against the occurrence of AIDS and non-AIDS events.